Tobacco smoking associates with NF1 mutations exacerbating survival outcomes in gliomas - Xi Li; Han Yan; Jun Wu; Longbo Zhang (BMC, 2022)
Abstract Tobacco smoking is associated with increased risks of nearly 20 types of cancer. Although the association between smoking and gliomas, the most prevalent type of adult brain tumor, is still unconclusive, here, we found that the frequency of NF1 mutations was significantly increased in the glioma patients with smoking history compared to non-smoking patients (24% vs. 10%, P = 0.021). NF1 acts as a tumor suppressor gene is highly mutated in gliomas. The TCGA data analysis indicated that glioma patients carrying NF1 somatic mutations have worse overall survival (median survival time: smoking 19.9 months vs. non-smoking 36.8 month; P = 0.0018). In addition, we revealed that the NF1 and IDH1 mutations were mutually exclusive suggesting NF1 mutation has independent molecular mechanism involved in glioma biology.